Methotrexate Enhances Apoptosis of Transmembrane TNF-Expressing Cells Treated With Anti-TNF Agents - Wang, Qiaolei; Oryoji, Daisuke; Mitoma, Hiroki; Kimoto, Yasutaka; Koyanagi, Masamichi; Yokoyama, Kana; Ayano, Masahiro; Akahoshi, Mitsuteru; Arinobu, Yojiro; Niiro, Hiroaki; Akashi, Koichi; Horiuchi, Takahiko (Frontiers in Immunology, 2020)
Background: Concomitant use of methotrexate (MTX) improves the clinical efficacy of anti-TNF agents in the treatment of rheumatoid arthritis (RA). We aimed to clarify the cytotoxic effect of MTX on transmembrane TNF (tmTNF)-expressing cells treated with anti-TNF agents. METHODS: Jurkat T cells stably expressing tmTNF were used for the following experiments. Cytotoxicity induced by an anti-TNF agent (infliximab, adalimumab, or certolizumab pegol) with concomitant MTX were compared with that by MTX alone or by an anti-TNF agent alone using flow cytometry. Apoptosis-induction mediated by reverse signal through tmTNF, complement-dependent cytotoxicity (CDC), antibody-dependent cell-mediated cytotoxicity (ADCC), and antibody-dependent cellular phagocytosis (ADCP) were evaluated. Folic acid and Y-27632, a Rho kinase inhibitor, were used as inhibitors to study intracellular signaling pathway in apoptosis induced by MTX and anti-TNF agents. RESULTS: Apoptosis of tmTNF-expressing cells was significantly increased by the concomitant administration of MTX and an anti-TNF agent, compared with MTX alone or an anti-TNF agent alone. The apoptosis induction by concomitant MTX was most pronounced in infliximab-treatment. Reverse signal transduction, but not CDC or ADCC/ADCP, was responsible for the coordinate effect of MTX and an anti-TNF agent on tmTNF-expressing cells. Folic acid inhibited MTX-mediated apoptosis, while Y-27632 suppressed JNK activation and infliximab-induced apoptosis via revere signal through tmTNF. CONCLUSION: The apoptotic effect was enhanced by combination of MTX and an anti-TNF agent in tmTNF-expressing cells. The intracellular pathways induced by MTX and anti-TNF agents seem to be independent. These findings might explain at least in part improved the clinical response upon co-therapy of MTX and an anti-TNF agent in RA.